2020
DOI: 10.3390/s20071820
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Type DNA Micro-Optode Based on Gold–Latex Spheres Label for Reflectance Dengue Virus Detection

Abstract: A DNA micro-optode for dengue virus detection was developed based on the sandwich hybridization strategy of DNAs on succinimide-functionalized poly(n-butyl acrylate) (poly(nBA-NAS)) microspheres. Gold nanoparticles (AuNPs) with an average diameter of ~20 nm were synthesized using a centrifugation-based method and adsorbed on the submicrometer-sized polyelectrolyte-coated poly(styrene-co-acrylic acid) (PSA) latex particles via an electrostatic method. The AuNP–latex spheres were attached to the thiolated report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…检测登革热病毒的荧光生物传感器, 在各种光学生 物传感器中最受欢迎, 因为这种传感方法具有高准确性 和敏感性 [65] . Oliveira 等 [87] 将荧光信号分子和寡核苷酸 组合构建了一种适体/核酸酶传感技术, 当捕获探针和 靶核酸特异性结合时, 可在 20 min 后释放出荧光信号, 通过核酸酶切割, 可实现信号放大.…”
Section: 荧光生物传感器unclassified
“…检测登革热病毒的荧光生物传感器, 在各种光学生 物传感器中最受欢迎, 因为这种传感方法具有高准确性 和敏感性 [65] . Oliveira 等 [87] 将荧光信号分子和寡核苷酸 组合构建了一种适体/核酸酶传感技术, 当捕获探针和 靶核酸特异性结合时, 可在 20 min 后释放出荧光信号, 通过核酸酶切割, 可实现信号放大.…”
Section: 荧光生物传感器unclassified
“…In biochemical sensors, an additional layer is added between the transducer and the recognition elements to reduce non-specific interaction, which is based on the white-light interference of visible radiation reflected on both interfaces of a layer [ 103 ]. A study by Jeningsih et al [ 104 ] has demonstrated a sandwich hybridization strategy of DNAs using a serotype-specific and ultrasensitive microspheres-based DNA opto-sensor to detect dengue virus (DENV). The succinimide-functionalized poly(n-butyl acrylate) (poly(nBA-NAS) microspheres were employed as the DNA hybridization platform and the gold-latex (AuNPs-PSA) sphere was employed as an optical amplification label.…”
Section: The Development Of Optical and Electrochemical Metal Nanoparticles-based Biosensors For The Detection Of Viral Rnamentioning
confidence: 99%
“…Based on the table, all the biosensors demonstrated high sensitivity with a low LOD in the range of fM to nM. The lowest LOD can be observed by the reflectance-based biosensor, which showed the LOD value of 1 × 10 −29 M via a sandwich recognition procedure [ 104 ]. However, the biosensor was susceptible to nucleic acid degradation, resulting in unexpected errors in actual nucleic acid detection.…”
Section: The Development Of Optical and Electrochemical Metal Nanoparticles-based Biosensors For The Detection Of Viral Rnamentioning
confidence: 99%
See 2 more Smart Citations